Purification and Characterization of Contemporaneously Produced Alkaline Protease and Î±-amylase Enzymes from Locally Isolated Bacillus methylotrophicus SCJ4 - El-Gendi, Hamada; Azab, Mohamed S.; El-Fakharany, Esmail M.; Soliman, Nadia A.; Abdel-Fattah, Yasser R. (PSM Biological Research, 2016)
The contemporaneously produced alkaline protease and Î±-amylase by locally isolated Bacillus methylotrophicus SCJ4 had been purified in two steps and some characteristics of the purified enzymes were studied. Crude enzymes were first salted out using ammonium sulfate, and then concentrated proteins were applied to anion column chromatography Q-sepharose (HiPrep Q FF 16/10 column). The purified alkaline protease has an estimated molecular mass of 24 kDa with maximum enzyme activity (1185U/ml/min) at pH 9.0 and 55ÂºC. This enzyme belongs to serine proteases family with remarkable stability up to 62% and 61.5% toward Sodium Dodecyl Sulfate (SDS) and Hg++ respectively. On the other hand, the purified amylase is a calcium-independent Î±-amylase, showing a good stability against SDS up to 73%. The estimated molecular mass was 67.5 kDa with maximum enzyme activity (280U/ml/min) at pH 7.0 and 65ÂºC.